AMANAT DALAM PANTUN ADAT PERKAWINAN MASYARAKAT DESA LOPAK ALAI KECAMATAN KUMPEH KABUPATEN MUARO JAMBI (ANALISIS STRUKTURAL) - Erlina Zahar; Siti Nurhaliza (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
Literary works are a means of communication for the delivery of values in guidance in a customary marriage. So that the guidance conveyed by the society is able to open the minds of  listeners. This research aims to describe the types of values, namely explicit and implicit values contained in the customary marriage of the society of Lopak Alai Village, Kumpeh Ulu Subdistrict, Muaro Jambi Regency. This type of research uses qualitative descriptive method, data collection techniques are carried out with documentation, observation, interviews, and record tapping. In this researc, the data is in the form of types of values, namely explicit and implicit values taken on the customary marriage of the people of Lopak Alai Village, Kumpeh Ulu Subdistrict, Muaro Jambi Regency. Based on the research that has been conducted on the values in the Customary Marriage of Lopak Alai Village, Kumpeh Ulu Subdistrict, Muaro Jambi Regency, the results of the research can be obtained as follows: (1) the explicit values occured in 38 expressions, (2) implicit values as many as 14 expressions.